2022
DOI: 10.1038/s41598-022-21112-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging-based lower limb muscle evaluation in Charcot-Marie-Tooth disease type 1A patients and its correlation with clinical data

Abstract: We aimed to derive comprehensive MRI parameters that reflect intramuscular fat infiltration severity for designated lower extremity levels, based on semiquantitative analyses in Charcot-Marie-Tooth disease type 1A (CMT1A) patients. We reviewed lower extremity MRIs of 116 CMT1A patients. Intramuscular fat infiltration grading using the Mercuri scale was performed for the non-dominant lower extremity at three levels (proximal, mid, and distal) for the thigh and at two levels (proximal and distal) for the lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
0
1
Order By: Relevance
“…The results demonstrated signi cant correlations between the semi-quantitative scoring and clinical parameters, particularly with functional disability scale (FDS score), 10-minute walk test (10-MWT) time, and disease duration, re ecting the progressive nature of intramuscular fat in ltration in CMT1A patients. However, it is worth noting that contrary to our study which found strong correlations in the thigh muscles, the CMT1A study revealed stronger correlations between clinical parameters and the semi-quantitative scoring obtained from the lower legs [40]. Undoubtedly, a more comprehensive investigation is warranted to examine the correlation between muscle functionality and the MRI parameter in VCP disease.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The results demonstrated signi cant correlations between the semi-quantitative scoring and clinical parameters, particularly with functional disability scale (FDS score), 10-minute walk test (10-MWT) time, and disease duration, re ecting the progressive nature of intramuscular fat in ltration in CMT1A patients. However, it is worth noting that contrary to our study which found strong correlations in the thigh muscles, the CMT1A study revealed stronger correlations between clinical parameters and the semi-quantitative scoring obtained from the lower legs [40]. Undoubtedly, a more comprehensive investigation is warranted to examine the correlation between muscle functionality and the MRI parameter in VCP disease.…”
Section: Discussioncontrasting
confidence: 93%
“…Interestingly, the same semi-quantitative method employed in our study has also proven successful in a recent investigation correlating disease severity in CMT1A [40]. The results demonstrated signi cant correlations between the semi-quantitative scoring and clinical parameters, particularly with functional disability scale (FDS score), 10-minute walk test (10-MWT) time, and disease duration, re ecting the progressive nature of intramuscular fat in ltration in CMT1A patients.…”
Section: Discussionsupporting
confidence: 56%